Quantitative Trait Locus Mapping of Acute Functional Tolerance in the LXS Recombinant Inbred Strains. (April 2015) - Bennett, Beth; Larson, Colin; Richmond, Phillip A.; Odell, Aaron T.; Saba, Laura M.; Tabakoff, Boris; Dowell, Robin; Radcliffe, Richard A.
<x xml:space="preserve">Abstract</x> Background We previously reported that acute functional tolerance (AFT) to the hypnotic effects of alcohol was significantly correlated with drinking in the dark (DID) in the LXS recombinant inbred panel, but only in mice that had been pretreated with alcohol. Here, we have conducted quantitative trait locus (QTL) mapping for AFT. DNA sequencing of the progenitor ILS and ISS strains and microarray analyses were also conducted to identify candidate genes and functional correlates. Methods LXS mice were given either saline or alcohol (5 g/kg) on day 1 and then tested for loss of righting reflex AFT on day 2. QTLs were mapped using standard procedures. Two microarray analyses from brain were conducted: (i) naïve LXS mice and (ii) an alcohol treatment time course in the ILS and ISS. The full genomes of the ILS and ISS were sequenced to a depth of approximately 30×. Results A significant QTL for AFT in the alcohol pretreatment group was mapped to distal chromosome 4; numerous suggestive QTLs were also mapped. Preference drinking and DID have previously been mapped to the chromosome 4 locus. The credible interval of the significant chromosome 4 QTL spanned 23 Mb and included 716 annotated genes of which 150 had at least 1 nonsynonymous single nucleotide polymorphism or small indel that differed between the ILS and ISS; expression of 48 of the genes was cis‐regulated. Enrichment analysis indicated broad functional categories underlying AFT, including proteolysis, transcription regulation, chromatin modification, protein kinase activity, and apoptosis. Conclusions The chromosome 4 QTL is a key region containing possibly pleiotropic genes for AFT and drinking behavior. Given that the region contains many viable candidates and a large number of the genes in the interval fall into 1 or more of the enriched functional categories, we postulate that many genes of varying effect size contribute to the observed QTL effect.